Pablo Escobar: ¿La fortaleza del héroe o el miedo causado por el terrorismo? (2021)
Many movies and TV series released in recent years have become very popular some chiefs of the drug trafficking. We find among them the well-known Colombian capo Pablo Escobar Gaviria. This paper, written originally for European readers, proposes a reflection about the figure of Escobar from the point of view of the virtue of courage. ¿Is a man like Escobar a heroic model of that cardinal virtue?